2021
DOI: 10.1007/s12369-021-00778-6
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Emotions in Human–Robot Interactions: Perspectives from Robotic Psychology on 20 Years of Research

Abstract: Knowledge production within the interdisciplinary field of human–robot interaction (HRI) with social robots has accelerated, despite the continued fragmentation of the research domain. Together, these features make it hard to remain at the forefront of research or assess the collective evidence pertaining to specific areas, such as the role of emotions in HRI. This systematic review of state-of-the-art research into humans’ recognition and responses to artificial emotions of social robots during HRI encompasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(32 citation statements)
references
References 269 publications
(469 reference statements)
1
30
0
1
Order By: Relevance
“…However, none has been transdisciplinary in nature and taken a service focus. Most reviews have restrictive foci: non‐verbal robotic communication (Saunderson & Nejat, 2019), emotions in HRI (Stock‐Homburg, 2021), service failure (Honig & Oron‐Gilad, 2018), first encounters (Avelino et al., 2021), ethical considerations related to HRI (Boada et al., 2021; Tan et al., 2021), social acceptance of robots in different occupational fields (Savela et al., 2018), social robots to combat loneliness (Gasteiger et al., 2021), or quantifiable evidence of human attitudes toward social robots (Naneva et al., 2020). Others have been restricted to a specific social robot model (i.e., NAO; Robaczewski et al., 2021) or context, such as elderly care (i.e., socially assistive robots [SAR]; Kachouie et al., 2014; Vandemeulebroucke et al., 2021; Wang et al., 2022), education (Woo et al., 2021), or hospitality (Ivanov et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, none has been transdisciplinary in nature and taken a service focus. Most reviews have restrictive foci: non‐verbal robotic communication (Saunderson & Nejat, 2019), emotions in HRI (Stock‐Homburg, 2021), service failure (Honig & Oron‐Gilad, 2018), first encounters (Avelino et al., 2021), ethical considerations related to HRI (Boada et al., 2021; Tan et al., 2021), social acceptance of robots in different occupational fields (Savela et al., 2018), social robots to combat loneliness (Gasteiger et al., 2021), or quantifiable evidence of human attitudes toward social robots (Naneva et al., 2020). Others have been restricted to a specific social robot model (i.e., NAO; Robaczewski et al., 2021) or context, such as elderly care (i.e., socially assistive robots [SAR]; Kachouie et al., 2014; Vandemeulebroucke et al., 2021; Wang et al., 2022), education (Woo et al., 2021), or hospitality (Ivanov et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Robots expressing emotions are also another aspect of interest in this area, as shown in [ 42 ]. That survey presented a review of research papers from 2000 to 2020 focused on studying the generation of artificial robotic emotions (stimulus), human recognition of robotic artificial emotions (organism), and human responses to robotic emotions (response), as a contribution to the robotic psychology area.…”
Section: Related Workmentioning
confidence: 99%
“…That survey presented a review of research papers from 2000 to 2020 focused on studying the generation of artificial robotic emotions (stimulus), human recognition of robotic artificial emotions (organism), and human responses to robotic emotions (response), as a contribution to the robotic psychology area. These works described in both surveys [ 41 , 42 ] demonstrated that social robotics is a growing area, where psychology and sociology aspects converge [ 8 ].…”
Section: Related Workmentioning
confidence: 99%
“…Robots and artificial agents are designed to demonstrate their identity using emotional expressions like speech, facial expressions, and head movements [e.g., 4, 5], which will influence on how a robot and its identity are perceived [6,7]. For example, previous studies show that robots that express positive emotions tend to be more accepted than robots that do not [8]. Speech is a central modality to convey emotions and information about one's identity to others.…”
Section: T Heme 1: P Hilosophymentioning
confidence: 99%